Pengaruh Kemampuan Kerja, Keterlibatan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan (Lokasi Riset Bertempat di PT. Karya Delta Permai Banjarmasin Kalimantan-Selatan) - Widya Pamela Rahmadani; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine and analyze the Effect of Work Ability, Work Involvement and Work Motivation on Employee Performance of PT. The work of Delta Permai Banjarmasin, South Kalimantan, simultaneously and partially. The population in this study amounted to 160 and a sample of 62 employees. Sampling needs to be done considering that the population is too large to determine the number of samples in this study using probability sampling that is proportionate stratified random sampling. Data collection techniques using a questionnaire (questionnaire). Data analysis using SPSS version 16.0 for windows. The analytical tool used in this study is the instrument test, normality test, classic assumption test, multiple linear regression analysis and hypothesis testing. The results of this study concluded that the variable Work Ability does not have an effect on employee performance partially while the work engagement variable has an influence on employee performance partially and motivation has an influence on employee performance partially. Work ability, work involvement and work motivation simultaneously influence employee performance.Keywords: Work Ability, Work Involvement and Work Motivation on Performance